2017
DOI: 10.1089/dna.2017.3664
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Single-Nucleotide Polymorphisms, the Expression of DNA Damage Response Genes, and Hepatocellular Carcinoma in a Polish Population

Abstract: The molecular mechanism of hepatocellular carcinoma (HCC) is related to DNA damage caused by oxidative stress products induced by hepatitis B virus (HBV) or C (HCV) infection and exposure to environmental pollutants. Single-nucleotide polymorphisms (SNPs) of DNA damage response (DDR) genes may influence individual susceptibility to environmental risk factors and affect DNA repair efficacy, which, in turn, can influence the risk of HCC. The study evaluates a panel of 15 SNPs in 11 DDR genes (XRCC1, XRCC3, XPD, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 87 publications
1
23
1
Order By: Relevance
“…The +4150G>A variant was associated with colorectal cancer in East Asians . No significant association between FEN1 −69G>A polymorphism and hepatocellular carcinoma was evident in a Polish population …”
Section: Discussionmentioning
confidence: 87%
“…The +4150G>A variant was associated with colorectal cancer in East Asians . No significant association between FEN1 −69G>A polymorphism and hepatocellular carcinoma was evident in a Polish population …”
Section: Discussionmentioning
confidence: 87%
“…Previous studies have reported that XRCC1 expression is elevated in colorectal [ 43 ], esophageal [ 44 ], and lung cancer tissues [ 45 ]. Similarly, Krupa et al [ 21 ] showed that the mRNA expression of XRCC1 in HCC tissues was significantly lower than that in adjacent non-lesional tissues. The expression of XRCC1 in cancer tissues is closely related to the intrinsic genetic phenotype.…”
Section: Discussionmentioning
confidence: 96%
“…11,34 After meticulous literature exploration for the articles that investigated the correlation of the APEX1 with the susceptibility of HCC. 25 However, several studies investigated the contribution of the APEX1 (rs1130409*p.Asp148Glu) variant with the elevated risk of multiple cancerous illnesses including renal cell carcinoma, 33 breast cancer, 14,35 osteosarcoma, 36 gastric cancer, 37 lung cancer, 11,12 prostate cancer, 38 pancreatic cancer, 39 oropharyngeal squamous cell carcinoma, 40 and bladder cancer. 41 Obviously, the APEX protein is thought to play an essential function in the oxidation-reduction activities of various transcription factors as well as the repair of the single-strand breaks that originated within the genome.…”
Section: Discussionmentioning
confidence: 99%